Sinus or nasal surgery alleviates headache symptoms: A prospective study - Vegard Bugten; Marte Fossum; Ann Helen Nilsen (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Introduction: The primary aim of this prospective study was to evaluate headache severity before and after surgery in patients with chronic rhinosinusitis without polyps (CRSsNP), chronic rhinosinusitis with polyps (CRSwNP), deviated nasal septum (DNS), and inferior turbinate hypertrophy (ITH). Our secondary aim was to compare the improvement of headache symptoms in these different patient groups. Methods: We enrolled 154 patients with CRSsNP, 130 patients with CRSwNP, 144 patients with DNS with or without ITH, and 69 patients with only ITH. Problems with headaches were reported on a visual analogue scale (VAS) preoperatively and six months postoperatively. Results: Patients with CRSsNP reported preoperatively signifi cantly more headaches on the VAS than the other patient groups. Headaches improved signifi cantly after surgery (p<0.001) but they improved more in CRSsNP patients than in other patient groups. Postoperatively, there were no signifi cant differences in headache problems between the groups. The CRSsNP group reported 50 (standard deviation [SD] 29) on the VAS preoperatively and 25 (SD 26) postoperatively, the CRSwNP group reported 28 (SD 30) versus 18 (SD 25), the DNS group reported 31 (SD 30) versus 17 (SD 24), and the ITH group reported 31 (SD 32) versus 19 (SD 25). Subgroup analyses identifi ed gender as a factor that has an infl uence on the headache.Female patients reported a mean VAS score of 49 (SD 31) preoperatively and 28 (SD 28) postoperatively. Male patients reported a mean VAS score of 29 (SD 29) preoperatively and 15 (SD 22) postoperatively.